Differentially Expressed Functional LncRNAs in Human Subjects With Metabolic Syndrome Reflect a Competing Endogenous RNA Network in Circulating Extracellular Vesicles - Li, Yongxin; Meng, Yu; Liu, Yuanhang; van Wijnen, Andre J.; Eirin, Alfonso; Lerman, Lilach O. (Frontiers in Molecular Biosciences, 2021)
Metabolic syndrome (MetS), a collective cluster of disease risk factors that includes dyslipidemia, obesity, inflammation, hypertension, and insulin resistance, affects numerous people worldwide. Accumulating studies have shown that long-noncoding RNAs (lncRNA) serve as competing endogenous RNA (ceRNA) to play essential roles in regulating gene expression in various diseases. To explore the role of lncRNAs as ceRNAs in MetS, we examined a MetS-associated network in circulating extracellular vesicles (EVs) collected from systemic blood of MetS and control patients (n=5 each). In total, 191 differentially-expressed (DE) lncRNAs, 1389 mRNAs, and 138 miRNAs were selected for further analysis. Biological processes and pathway functional enrichment analysis were performed based on the Database for Annotation, Visualization, and Integrated Discovery (DAVID) database. LncRNA/mRNA/miRNA ceRNA network was constructed by Cytoscape v3.8 based on the DE-RNAs, and included 13 lncRNAs, 8 miRNAs, and 64 mRNAs. MetS patients showed elevated body-weight, glucose, blood pressure, insulin, liver injury and inflammatory markers levels. We found that lncRNAs reflect a ceRNA network that may regulate central cellular processes and complications of MetS, including cancer. These findings suggest that MetS alters the interactions among the ceRNA network components in circulating EVs and that this cargo of circulating EVs may have potential translational ramifications for MetS.